The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.jctb.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Nonnegative k-sums, fractional covers, and probability of small deviations

Abstract: More than twenty years ago, Manickam, Miklós, and Singhi conjectured that for any integers n, k satisfying n ≥ 4k, every set of n real numbers with nonnegative sum has at least n−1 k−1 kelement subsets whose sum is also nonnegative. In this paper we discuss the connection of this problem with matchings and fractional covers of hypergraphs, and with the question of estimating the probability that the sum of nonnegative independent random variables exceeds its expectation by a given amount. Using these connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 15 publications
(26 reference statements)
2
48
0
Order By: Relevance
“…The main result of this paper verifies Conjecture 1.1 when n ≥ 8k 2 . In particular, Theorem 1.2 simultaneously improves and simplifies the bound n ≥ min{33k 2 , 2k 3 } of Alon, Huang, and Sudakov [2] and also the bound n ≥ 10 46 k of Pokrovskiy [20] when k < 10 45 . Note that there is no loss of generality in assuming that the n real numbers in Conjecture 1.1 are listed in decreasing order and sum to zero.…”
mentioning
confidence: 83%
“…The main result of this paper verifies Conjecture 1.1 when n ≥ 8k 2 . In particular, Theorem 1.2 simultaneously improves and simplifies the bound n ≥ min{33k 2 , 2k 3 } of Alon, Huang, and Sudakov [2] and also the bound n ≥ 10 46 k of Pokrovskiy [20] when k < 10 45 . Note that there is no loss of generality in assuming that the n real numbers in Conjecture 1.1 are listed in decreasing order and sum to zero.…”
mentioning
confidence: 83%
“…The conjecture also has applications to the Manickam-Mikós-Singhi conjecture in number theory (for details see e.g. [2]). Despite its seeming simplicity Conjecture 1.1 is still wide open in general.…”
Section: Large Matchings In Hypergraphs With Many Edgesmentioning
confidence: 99%
“…Tyomkyn [21] improved this bound to n ≥ k(4e log k) k ≈ e ck log log k . Recently Alon, Huang, and Sudakov [2] showed that the conjecture holds when n ≥ 33k 2 . Subsequently Frankl [8] gave an alternative proof of the conjecture in a range of the form n ≥ 3k 3 /2, and Chowdhury, Sarkis, and Shahriari [7] gave a proof of the conjecture in the range of the form n ≥ 8k 2 .…”
Section: Introductionmentioning
confidence: 98%